Skip to content

Commit

Permalink
changed equations to align
Browse files Browse the repository at this point in the history
  • Loading branch information
andybeet committed Aug 13, 2024
1 parent 804aa6a commit c5bd4d1
Showing 1 changed file with 10 additions and 9 deletions.
19 changes: 10 additions & 9 deletions vignettes/Equations.Rmd
Original file line number Diff line number Diff line change
Expand Up @@ -27,29 +27,30 @@ library(arfit)
```


\begin{equation}
\begin{align}
\tag{1}
Y_t = \beta_0 + \beta_1 t + \epsilon_t
\end{equation}
\end{align}

---

\begin{equation}

\mathrm{L}\left( \underline{\theta}; \underline{y} \right )= \prod^n_{t=2} p\left(Y_t = y_t | Y_{t-1}=y_{t-1}\right) p\left(Y_1=y_1 \right) (\#eq:two)
\begin{align}
\tag{2}
\mathrm{L}\left( \underline{\theta}; \underline{y} \right )= \prod^n_{t=2} p\left(Y_t = y_t | Y_{t-1}=y_{t-1}\right) p\left(Y_1=y_1 \right)
\end{equation}

---

\begin{align}
\tag{3}
logL\left( \underline{\theta}; \underline{y} \right ) = & -\frac{n}{2}log2\pi - nlog\sigma + \frac{1}{2}log(1-\phi^2) \notag \\
& -\frac{1}{2\sigma^2}\left( (1-\phi^2)(y_1-\beta_0-\beta_1)^2 + \sum^n_{t=2}(y_t - \phi y_{t-1}-\beta_0(1-\phi^2) -t\beta_1 + \phi(t-1)\beta_1)^2 \right) (\#eq:three)
& -\frac{1}{2\sigma^2}\left( (1-\phi^2)(y_1-\beta_0-\beta_1)^2 + \sum^n_{t=2}(y_t - \phi y_{t-1}-\beta_0(1-\phi^2) -t\beta_1 + \phi(t-1)\beta_1)^2 \right)
\end{align}

---

\begin{equation}
\hat\sigma^2 = \frac{1}{n}\left( (1-\phi^2)(y_1-\beta_0-\beta_1)^2 + \sum^n_{t=2}(y_t - \phi y_{t-1}-\beta_0(1-\phi^2) - t\beta_1 + \phi(t-1)\beta_1)^2 \right) (\#eq:four)
\hat\sigma^2 = \frac{1}{n}\left( (1-\phi^2)(y_1-\beta_0-\beta_1)^2 + \sum^n_{t=2}(y_t - \phi y_{t-1}-\beta_0(1-\phi^2) - t\beta_1 + \phi(t-1)\beta_1)^2 \right)
\end{equation}

---
Expand All @@ -59,7 +60,7 @@ logL\left( \underline{\beta}, \phi; \underline{y} \right ) &= const. + \frac{1}{
&-\frac{n}{2}log\left( (1-\phi^2)(y_1-\beta_0-\beta_1)^2 + \sum^n_{t=2}(y_t - \phi y_{t-1}-\beta_0(1-\phi^2)-t\beta_1 + \phi(t-1)\beta_1)^2 \right) \\

&= const. + \frac{1}{2}log(1-\phi^2) \notag \\
&-\frac{n}{2}log\left( (1-\phi^2)(y_1-X_1\underline{\beta})^2 + \sum^n_{t=2}(y_t - \phi y_{t-1}-X_t\underline{\beta} + \phi X_{t-1}\underline{\beta})^2 \right) (\#eq:five)
&-\frac{n}{2}log\left( (1-\phi^2)(y_1-X_1\underline{\beta})^2 + \sum^n_{t=2}(y_t - \phi y_{t-1}-X_t\underline{\beta} + \phi X_{t-1}\underline{\beta})^2 \right)
\end{align}

---
Expand All @@ -69,7 +70,7 @@ logL\left( \underline{\beta}, \underline{\phi},\sigma; \underline{y} \right ) &=
\\
&-\frac{1 }{2 \sigma^2} (\underline{y_p}-\underline{\mu_p})^T V_p^{-1}(\underline{y_p}-\underline{\mu_p}) \\

&- \frac{1}{2\sigma^2}\sum^n_{t=p+1} (y_t - c - \phi_1y_{t-1} - ... - \phi_p y_{t-p})^2 \\ (\#eq:six)
&- \frac{1}{2\sigma^2}\sum^n_{t=p+1} (y_t - c - \phi_1y_{t-1} - ... - \phi_p y_{t-p})^2

\end{align}

Expand Down

0 comments on commit c5bd4d1

Please sign in to comment.